GIRL-CHILD EDUCATION FOR HEALTHY LIVING: AN APPRAISAL - Usman, I. G. (Sokoto Educational Review, 2014)
Girl-child education and school attendance are the focus of the United Nations agencies in recent years because education is the key to the advancement of girls and women, as World wide Hasli (2006) noted that globally, world vision has joined with communities to ensure that neither violence; disability nor other terms of discrimination will prevent women and girls from enjoying their rights. The Federal Government of Nigeria (FGN, 2004) in the national policy on education stated that education is a right and not a privilege for every citizen, whether male or female. It is against this backdrop that this paper attempts to appraise the girl-child education on the basis of improved life condition, healthy living and general development of individual and society. In pursuing the goals of the Millennium Development Goals (MDGs), many nations of the world have put machinery in place, to encourage the girl-child education. This paper is interested in emphasising on girl - child education so as to actualise women potentials and those significant areas that contribute to the welfare and sustainability of the girl - child. The paper also advanced counselling strategies such as mentoring, modelling and value orientation which could serve as a panacea for encouraging girl-child education in Nigeria.